Поверхневi напруження на початкових етапах окислення GexSi1−x/Si(001) - Grynchuk, A. A.; Koval, I. P.; Nakhodkin, M. G. (Publishing house "Academperiodika", 2018)
Elastic stresses arising at the clean GexSi1−x/Si(001) surface, as well as at the initial stages of its oxidation, are considered qualitatively by analyzing the changes of unit cell dimensions occurring owing to the ad-dimer formation or the atomic or molecular adsorption on the unit cell surfaces. The stress character is found to be almost identical for the clean GexSi1−x/Si(001) surface and the GexSi1−x/Si(001) surface with adsorbed oxygen molecules or one to three adsorbed oxygen atoms. In addition, the surface stresses revealed a significant anisotropy: they turned out compressive along the dimer rows and three times as large as tensile stresses in the perpendicular direction (along the interdimer bonds).